2016
DOI: 10.18276/cej.2016.2-06
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Acceleration Activity in Competitive Youth Soccer

Abstract: abstract. Soccer match-play is increasingly characterised by short, high-speed bursts reliant on the ability to accelerate. Performance is impaired after peak acceleration activity and during the second half and may compromise a player's effectiveness. To date, information about repeated acceleration sequences is lacking but would provide further insight into high-speed activity during competition. This study examined repeated acceleration ability (RAA) using GPS (5 Hz) and accelerometer (100 Hz), during 14 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Up to now, few studies in football have investigated multiple acceleration variables, simultaneously (Barberó-Álvarez et al, 2014 ; Barron et al, 2016 ; Sonderegger et al, 2016 ; Abbott et al, 2018a , b ; Serpiello et al, 2018 ; Delaney et al, 2019 ; Martínez-Cabrera et al, 2021 ). Commonly used acceleration variables—including high-intensity efforts (Sonderegger et al, 2016 ; Abbott et al, 2018a , b ; Martínez-Cabrera et al, 2021 ), repeated bouts (Barberó-Álvarez et al, 2014 ; Barron et al, 2016 ; Serpiello et al, 2018 ), and average acceleration (Delaney et al, 2018 , 2019 )—have typically been investigated in isolation, with each variable suffering from unique limitations. Subsequently, any findings may provide a limited representation of what specific acceleration demands had actually occurred.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, few studies in football have investigated multiple acceleration variables, simultaneously (Barberó-Álvarez et al, 2014 ; Barron et al, 2016 ; Sonderegger et al, 2016 ; Abbott et al, 2018a , b ; Serpiello et al, 2018 ; Delaney et al, 2019 ; Martínez-Cabrera et al, 2021 ). Commonly used acceleration variables—including high-intensity efforts (Sonderegger et al, 2016 ; Abbott et al, 2018a , b ; Martínez-Cabrera et al, 2021 ), repeated bouts (Barberó-Álvarez et al, 2014 ; Barron et al, 2016 ; Serpiello et al, 2018 ), and average acceleration (Delaney et al, 2018 , 2019 )—have typically been investigated in isolation, with each variable suffering from unique limitations. Subsequently, any findings may provide a limited representation of what specific acceleration demands had actually occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to repeatedly accelerate amidst short recoveries may also be important in football (Barron et al, 2016 ; Serpiello et al, 2018 ). Literature investigating repeat high-intensity accelerations in football found that repeated bouts occur frequently in matches (Barron et al, 2016 ; Serpiello et al, 2018 ), suggesting their importance and subsequent need for development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation